Analysis of Polyphosphate during the Enhanced Biological Phosphorus Removal process using Fourier Transform Infrared (FTIR) spectroscopy - wang Rong; Ma Yuanyuan; Zhang Di; Li Weihua (E3S Web of Conferences, 2020)
Two enhanced biological phosphorus removal (EBPR) reactors were operated in synthetic wastewater with different Chemical Oxygen Demand/Phosphorus (COD/P) ratios. The sludge samples at different sample times were lyophilized and characterized by Fourier Transform Infrared (FTIR) spectroscopy. Results showed that the infrared spectral curves from two reactors were similar but the intensities were different at specific wavenumbers. The spectral intensities at 1260cm-1 and 890cm-1 of the sludge samples from the reactor at low COD/P ratios were relatively stronger, but those of the reactor at high COD/P ratios were relatively weaker. The principal component projection plot of FTIR spectra analyzed with principal components analysis (PCA) showed that the sludge samples at the same COD/P ratios assembled together implicating the principal component projection plot could discriminate the sludge samples from different reactor. The infrared peak near 890cm-1 was separated and integrated with Gaussian peak fitting method. The integrated areas were correlated to the polyphosphate content in the sludge. Results showed that the prediction values were in good accordance with those determined by chemical method. This work provides a new method for the recognition of polyphosphate in sludge and provides a basis for the rapid determination of polyphosphate.